The Effect of Pili Protein of Klebsiella pneumoniae 65,5 kDa on Enhanced IFN- Gamma Levels in Mice Liver - Dini Agustina; Zahrah Febianti; Enny Suswati; Diana Chusna Mueida; Muhammad Ali Shodikin; Samudra Ayu (Indonesian Society for microbiology, 2023)
Klebsiella pneumoniae develops antibiotic resistance by producing enzymes such as Extended-Spectrum Beta-Lactamase and Carbapenemase. Antibiotic resistance causes K. pneumoniae to have less antibiotic activity and more virulence factors. Capsule polysaccharides, lipopolysaccharide, Outer Membrane Protein, siderophores, and pili are all virulence factors in K. pneumoniae. This study aims to demonstrate the possibility of a host immunological response to the pili protein K. pneumoniae 65.5 kDa by injecting it into mice and measuring the levels of IFN-gamma cytokines in the mice's liver. This study used mice liver samples taken from 21 mice aged 6-8 weeks in the experimental investigation with a randomized post-test only controlled group design. Phosphate buffer saline was given to KI, pili protein antigen 65.5 kDa + Freunds' adjuvant was given to K2, and Freunds' adjuvant was given to K3. IFN-gamma concentration was measured using the sandwich ELISA method. The average concentration of IFN-gamma in the mice liver in this study was 247.68±47.67 pg m 'L ', 163.19±13.63 pg m'L', and 182.41 ±41.70 pg m'L'. The p-value of the Welch ANO VA test was 0.005 (p < 0.05), hence the Post Hoc Games-Howell test was used. The Games-Howell test showed a statistically significant difference in the mean value of IFN-gamma in KI compared to K2 and K3 of 0.007 and 0.046, respectively. There was no statistically significant difference between K2 and K3 with a p-value of 0.511. These findings revealed that intraperitoneal injection of Klebsiella pneumoniae pili protein 65.5 kDa did not increase IFN-gamma levels in the mice liver.